NEW INNOVATIVE TECHNOLOGIES IN EARLY DIAGNOSTICS, PREVENTION, PREDICTION OF PRECANCER AND CANCER DISEASES OF THE CERVIC. - Isakova Dilnoza Bakhtiyarovna (Scholar Express Journals, 2023)
Cervical cancer (CC) is considered to be one of some oncological diseases, which, when diagnosed at an early stage, can be effectively treated, which increases overall and recurrence-free survival, improves the quality of life of patients, and reduces the cost of treatment. The cause of cervical cancer is the human papillomavirus (HPV) of oncogenicgenotypes, which can be prevented by screening tests
Keywords: diseases of the cervix; oncogenic types of HPV; early diagnosis; minimally invasive method